Investigating the Functions of Meta-Discourse Markers in Arabic Academic Writing: A Comparative Study of Iranian and Arab Writers - Mahdi Moqadasi Nia; Rasool Dehghanzad (Ijaz Arabi Journal of Arabic Learning, 2026)
The present study aims to investigate the differences between Iranian (Persian-speaking) and Arab writers in the use of meta/discourse markers in Arabic academic writing. Emphasizing analysis at both the functional and individual marker levels, this study sought to answer the main research question of whether a significant difference exists between the two groups of writers in their use of meta/discourse markers. The research methodology was quantitative and corpus-based. The data comprised 200 academic article abstracts in the humanities and social sciences, selected through purposive sampling (100 abstracts by Iranian writers and 100 abstracts by Arab writers). meta/discourse markers were classified into 12 functions and 87 individual markers based on an integrated framework drawing on models by Fraser (2006) and Hyland (2005). Data were analyzed using Generalized Linear Models with a negative binomial distribution in SPSS software.The findings revealed that at the functional level, the pattern of discourse marker use did not differ significantly between the two groups (p = 0.063), with both groups employing additive, referential, explanatory, and introductory functions most frequently. However, at the level of individual markers, a significant difference was observed between the two groups (p 0.001). The marker wa (‘and’) was the most frequent marker overall, accounting for 38.1% of all uses, and was used significantly more often by Arab writers. Arab writers also made significantly greater use of the markers bal (contrastive), min khilāl (referential), qad (hedging), and mithl (explanatory). In contrast, Iranian writers employed introductory verbal markers such as yatanāwal, yuḥāwil, and yas‘ā, as well as inferential markers like aẓharat natā’ij... and tawuṣṣala, significantly more frequently.